Extended eco-efficient supply chain integration management model: A research note - Latifah Naina, Mohamed; Fernando, Yudi; Muhammad Shabir, Shaharudin (Penerbit Universiti Malaysia Pahang, 2019)
Manufacturing organizations must improve its environmental protection as this is the requirement of every stakeholder nowadays. At the same time, manufacturing organizations that pursue environmental protection goal should adopt eco-efficient supply chain integration as it has been known to improve environmental protection without sacrificing economic and operational performances. Nevertheless, there is a decline in integration among manufacturing organizations and its supply chain partners. Furthermore, investigations in the literature has been one-dimensional toward relationship between practice and performance. It is obvious that current studies pointing toward energy efficient practice to achieve eco-efficient supply chain integration but it is insufficient. Thus, this study objective is to investigate the impact of ecoefficient supply chain integration on environmental protection and proposing improvement for future research. This study has proposed an extended eco-efficient supply chain integration management model based on the gap in the literature and industry. This study elaborates on the importance of manufacturing organizations achieving environmental protection while understand that organizations especially from developing countries cannot afford to move from economic and operational performances. The extended model proposed also underlines the improvement for eco-efficient supply chain integration management model and providing breakthrough for future research to contribute to the organizational theory development and practical improvements.